Indications and Outcomes of Tracheostomy in Children After Congenital Heart Surgery - Pınar Yazıcı Özkaya; Eşe Eda Turanlı; İrem Ersayoğlu; Osman Nuri Tuncer; Bülent Karapınar (Journal of Pediatric Emergency and Intensive Care Medicine)

(untitled)
Introduction:In a minority of children after cardiovascular surgery may require prolonged mechanical ventilatory support and tracheostomy. We aim to describe indications, timing and, outcomes of the tracheostomy.Methods:A retrospective review of 12 children requiring tracheostomy after cardiac surgery between January 2010-December 2019 was performed. The patients’ characteristics, indications and timing for tracheostomy, and survival were reviewed.Results:After cardiac surgery, 12 (0.5%) of 2.459 patients with a median age at surgery of 210 days (interquartile range: 75-262 days) underwent tracheostomy. The median time between cardiac surgery and tracheostomy was 25 days (interquartile range: 15-47 days). Diaphragmatic paralysis was the most common (42%) indication for tracheostomy. Genetic syndrome or at least one non-cardiac morbidity was present in 41.6% of patients. The duration of mechanical ventilation was shorter in patients who had tracheostomy within 30 days compared with >30 days following intubation (30 vs. 60 days, p=0.035). The median length of pediatric intensive care unit stays after the tracheostomy was 41 days (range, 21-289 days). Among all patients with congenital heart surgery undergoing tracheostomy, 6 (50%) of 12 were decannulated after a median time of 179 days (range, 34-463 days). The operative mortality was 8.3% (1/12) and the overall mortality during the first year of follow-up was 8.3% (1/12).Conclusion:An early tracheostomy procedure may facilitates the weaning process and shorten the duration of positive pressure ventilation.